A method for effectively controlling abnormally high hydrogen content in molten steel

By controlling the particle size and warehouse discharge time of the top slag lime, the problem of difficult control of the hydrogen content in the molten steel under non-vacuum conditions is solved, and the hydrogen content in the molten steel is effectively reduced, and the quality and production efficiency of steel are improved.

CN119776613APending Publication Date: 2025-04-08SD STEEL RIZHAO CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411822331.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Under non-vacuum conditions, the hydrogen content in the molten steel is difficult to stabilize within 4 ppm, especially in humid environments, which affects the quality and production efficiency of the steel.

Method used

By controlling the particle size and addition timing of the top slag lime, especially the warehouse outlet time and atmospheric relative humidity of the top slag lime, the conversion ratio of CaO after moisture absorption is reduced, thereby reducing the hydrogen content in the molten steel.

Benefits of technology

It effectively reduces the hydrogen content in the molten steel and controls it to below 4.3ppm, improves the quality and production efficiency of steel, and reduces equipment investment and operating costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776613A_ABST
    Figure CN119776613A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of metal smelting, and in particular to a method for effectively controlling abnormally high hydrogen content in molten steel. After converter smelting is completed, the amount of top slag lime added is 400-1000kg; the particle size of the top slag lime is 20-30mm; the time T of the top slag lime to be discharged from the warehouse is controlled within the following range:; wherein, the unit of T is h; R is the relative humidity of the atmosphere; d is the average particle size of the top slag lime, in mm; after control, the hydrogen content in the molten steel arriving at the LF refining furnace is ≤4.3ppm. The present invention effectively reduces the hydrogen content in the molten steel by controlling the particle size and the time T of the top slag lime to be discharged from the warehouse while ensuring that the quality of the product steel is not affected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal smelting, and in particular to a method for effectively controlling abnormally high hydrogen content in molten steel. Background Art

[0002] During the converter steelmaking process, if the content of sulfur, phosphorus, oxygen, nitrogen and other elements in the molten steel is too high, the quality of the steel will be reduced, affecting the subsequent processing and use. Adding top slag lime can neutralize the sulfur, phosphorus and other impurity elements in the steel, reduce the oxygen content in the steel, thereby adjusting the chemical environment in the molten steel and improving the quality of the steel.

[0003] Hydrogen is one of the important factors that cause steel material failure. Studies have shown that hydrogen in steel has a significant impact on mechanical properties such as strength limit, cross-sectional shrinkage, elongation, impact toughness, and hot formability. Generally, the industry considers that when the hydrogen content in molten steel reaches or exceeds 7ppm, it is considered to be abnormally high. When the hydrogen content in non-vacuum treated molten steel reaches or exceeds 7ppm, the probability of mold sticking alarm and even steel leakage in the continuous casting process increases significantly, causing great trouble to the production and quality of steelmaking.

[0004] During the steelmaking process in coastal and riverside cities with high air humidity during the rainy season, the problem of abnormally high hydrogen content is common, and the hydrogen content in the molten steel of individual furnaces may even exceed 9ppm. The prior art usually uses a method of degassing under vacuum conditions to reduce the hydrogen content in the molten steel, using vacuum to reduce the solubility of hydrogen in the molten steel and accelerate the escape of hydrogen, thereby effectively reducing the hydrogen content in the molten steel. Although this method has a good dehydrogenation effect, it has large equipment investment, high operating costs, and low production efficiency. In addition, the molten steel will also experience a large temperature drop in a vacuum environment, resulting in poor fluidity and affecting subsequent casting and molding processes. Reducing the hydrogen content in the molten steel under non-vacuum conditions can significantly reduce equipment investment and operating costs and improve production efficiency. However, for non-vacuum treated molten steel, it is still a difficult problem to stably control the hydrogen content in the molten steel within 4ppm.

[0005] Invention patent CN117305536B discloses a method for producing ultra-low hydrogen content steel under non-vacuum conditions, which realizes the production of ultra-low hydrogen content (H < 0.0002ppm) steel under non-vacuum conditions by drying the raw materials, baking the steel ladle and the continuous casting tundish, weak cooling control, and extending the slow cooling time. This patent requires drying or baking the raw materials, steel ladle, and continuous casting tundish, which consumes a lot of energy and has a long production cycle. If the baked device is not used in time, it is easy to absorb moisture. If it is used while hot, it will cause local overheating of molten steel or billet, affecting the quality of the product steel. Summary of the invention

[0006] In view of the technical problem that the hydrogen content in non-vacuum treated molten steel is difficult to be stably controlled within 4ppm in a humid environment, the present invention provides a method for effectively controlling the abnormally high hydrogen content in molten steel, by controlling the particle size and addition timing of top slag lime, the hydrogen content in the molten steel is effectively reduced while ensuring that the quality of the product steel is not affected.

[0007] The technical solution of the present invention is as follows: A method for effectively controlling abnormally high hydrogen content in molten steel, after converter smelting is completed, the amount of top slag lime added is 400-1000kg; the particle size of the top slag lime is 20-30mm; the time T of the top slag lime being discharged from the warehouse is controlled within the following range: ; Among them, the unit of T is h; R is the relative humidity of the atmosphere; d is the average particle size of the top slag lime, in mm; after control, the hydrogen content in the molten steel reaching the LF refining furnace is ≤4.3ppm.

[0008] Furthermore, when the water absorption ratio of the top slag lime is ≤0.6%, the top slag lime is added during the steel tapping process 3 minutes after the deoxidizing alloy is added or after the converter steel tapping is completed.

[0009] Furthermore, the warehouse discharge time T is the time that the top slag lime is exposed to the atmosphere from the time of being discharged from the warehouse, that is, the time from the time of the top slag lime being discharged from the warehouse to the time of entering the converter, and the relative humidity of the atmosphere is 50%-80%.

[0010] Furthermore, during the steel tapping process of the converter, argon gas is blown into the bottom of the ladle until the ladle begins to be lifted.

[0011] Furthermore, the flow rate of bottom blowing argon is 40-80Nm 3 / h.

[0012] Furthermore, during the steel tapping process, the flow rate of argon gas blown from the bottom of the ladle is 60-80Nm 3 / h; 3-5min before the completion of steel tapping, the flow rate of argon gas at the bottom of the ladle is 60-80Nm 3 / h; from the end of steel tapping to the start of lifting the ladle, the flow rate of argon gas blowing from the bottom of the ladle is 40-60Nm 3 / h. In the early stage of steel tapping, the flow rate of argon gas blown from the bottom of the ladle is controlled at 60-80Nm 3 / h, which can ensure that the slag washing and deoxidation of the molten steel are more complete during the steel tapping process; after the steel tapping is completed, the flow rate of argon gas blown from the bottom of the ladle is appropriately reduced, which can make the composition of the molten steel more uniform and promote the collision, growth and floating of inclusions.

[0013] Further, the ladle is hoisted to the LF refining furnace for refining.

[0014] Furthermore, after control, the hydrogen content in the molten steel reaching the LF refining furnace is 2.3-2.8ppm.

[0015] Furthermore, after the molten steel arrives at the LF refining furnace, slag-making material is first added, and then argon is blown from the bottom of the ladle for stirring for 3-5 minutes. After the slag-making material is fully melted, the temperature is raised and the power is turned on. Argon is blown from the bottom of the ladle to promote the decomposition of Ca(OH)2 in the refined slag to generate CaO at high temperature, fully releasing OH - ions, avoiding OH remaining in the refined slag - The hydrogen produced by the decomposition of ions at high temperatures enters the molten steel.

[0016] The beneficial effects of the present invention are: The method provided by the present invention effectively controls the abnormally high hydrogen content in molten steel, controls the discharge time and average particle size of the top slag lime, reduces the conversion ratio of CaO in the top slag lime to Ca(OH)2 after absorbing moisture, and effectively reduces the hydrogen content in the molten steel while ensuring that the quality of the product steel is not affected. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0018] Figure 1 It is a scatter plot of the hydrogen content in each heat of molten steel in each experiment in experimental group 1.

[0019] Figure 2 It is a scatter plot of the hydrogen content in each heat of molten steel in each experiment in Experimental Group 2.

[0020] Figure 3 It is a scatter plot of the hydrogen content in each heat of molten steel in each experiment of experimental group 3.

[0021] Figure 4 It is a scatter plot of the hydrogen content in each heat of molten steel in each experiment in experimental group 4.

[0022] Figure 5 It is a scatter plot of the hydrogen content in each heat of molten steel in each experiment in experimental group 5.

[0023] Figure 6 It is the data fitting image of the average value of hydrogen content in molten steel of each heat in experimental group 5.

[0024] Figure 7 It is a statistical graph showing the average weight of the top slag lime of experimental group 1' to experimental group 3' changing with the explosion time.

[0025] Figure 8 It is a statistical graph showing the average weight of the top slag lime of experimental groups 4' to 6' changing with the explosion time.

[0026] Fig. 9 It is a statistical chart of moisture absorption rate of top slag lime of experimental group 1'-experimental group 6'. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0028] Example 1 Correlation experiment between hydrogen content in molten steel and the conversion ratio of CaO in lime to Ca(OH)2 after moisture absorption The moisture content of raw dolomite, sintered ore, light-burned magnesium balls and top slag lime was tested, and the test results are shown in Table 1.

[0029] Table 1 Water content of different non-metallic materials

[0030] Combined with the moisture content test results of different non-metallic materials in Table 1, an experimental plan was designed for different addition amounts of non-metallic materials. In the experimental plan, the timing and amount of adding recarburizer, raw dolomite, sintered ore, light-burned magnesium balls and top slag lime are shown in Table 2.

[0031] Table 2 Timing and amount of adding different non-metallic materials in different heats

[0032] The test plan is as follows: Experimental group 1: Four converters of the same specifications were marked as furnace 1-1, furnace 1-2, furnace 1-3 and furnace 1-4, and without adding raw dolomite, sintered ore, light-burned magnesium balls and top slag lime into the converters, during the steelmaking process, 0 kg, 50 kg, 100 kg and 200 kg of recarburizer were added to furnace 1-1, furnace 1-2, furnace 1-3 and furnace 1-4, respectively.

[0033] Experimental group 2: Four converters of the same specifications were marked as furnace 2-1, furnace 2-2, furnace 2-3 and furnace 2-4, and no sintered ore, light-burned magnesium balls, top slag lime and carburizer were added during the converter smelting and steelmaking process. Before slag splashing, 0 kg, 1000 kg, 2000 kg and 4000 kg of raw dolomite were added to furnace 2-1, furnace 2-2, furnace 2-3 and furnace 2-4 respectively.

[0034] Experimental group 3: Four converters of the same specifications were marked as furnace 3-1, furnace 3-2, furnace 3-3 and furnace 3-4, without adding raw dolomite splashing slag before converter smelting, and without adding light-burned magnesium balls, carburizers and top slag lime during converter smelting and steelmaking. In the early stage of converter blowing, 0kg, 300kg, 600kg and 1000kg of sintered ore were added to furnace 3-1, furnace 3-2, furnace 3-3 and furnace 3-4 respectively.

[0035] Experimental Group 4: Four converters of the same specifications were marked as furnace 4-1, furnace 4-2, furnace 4-3 and furnace 4-4, without adding raw dolomite splashing slag before converter smelting, and without adding sintered ore, top slag lime and carburizer during converter smelting and steelmaking. In the early stage of converter blowing, 0kg, 500kg, 1000kg and 2000kg of light-burned magnesium balls were added to furnace 4-1, furnace 4-2, furnace 4-3 and furnace 4-4 respectively.

[0036] Experimental group 5: Four converters of the same specifications were marked as furnace 5-1, furnace 5-2, furnace 5-3 and furnace 5-4, and no raw dolomite, sintered ore, light-burned magnesium balls and carburizer were added before and during the converter smelting process. During the converter tapping process, 0 kg, 400 kg, 600 kg and 800 kg of top slag lime were added to furnace 5-1, furnace 5-2, furnace 5-3 and furnace 5-4 respectively.

[0037] Experimental Group 6: Six converters of the same specifications were marked as furnace 6-1, furnace 6-2, furnace 6-3, furnace 6-4, furnace 6-5, and furnace 6-6. When 1 / 3 of the steel had been tapped, deoxidation alloy was added to the molten steel for deoxidation alloying. The average particle size of the top slag lime used in Experimental Group 6 was 30 mm, and the relative humidity of the atmosphere was 67%. The average particle size of the top slag lime and the relative humidity of the atmosphere were substituted into the following formula to calculate the range of the top slag lime tapping time T: ; T≤4.133h; Wherein, R is the relative humidity of the atmosphere; d is the average particle size of the top slag lime, in mm.

[0038] 800 kg of top slag lime with a discharge time of less than 4 hours was added to furnace 6-1, furnace 6-2 and furnace 6-3 respectively during the steel tapping process before adding the deoxidizing alloy, during the steel tapping process 3 minutes after the deoxidizing alloy was added, and after the steel tapping was completed; 800 kg of top slag lime with a discharge time of more than 8 hours was added to furnace 6-4, furnace 6-5 and furnace 6-6 respectively during the steel tapping process before adding the deoxidizing alloy, during the steel tapping process 3 minutes after the deoxidizing alloy was added, and after the steel tapping was completed. Three repetitions were set for each heat.

[0039] There is no specific plan for the metal materials in Experimental Groups 1 to 6. The amount of metal materials added is determined according to the actual amount of molten steel in the on-site production process. After the molten steel in Experimental Groups 1 to 6 enters the LF furnace for refining, hydrogen determination is immediately performed. The scatter plots of the hydrogen content of the molten steel in each experiment in Experimental Groups 1 to 5 are shown as follows: Figure 1-Figure 5 shown.

[0040] Depend on Figure 1 It can be seen that the hydrogen content in the molten steel with different addition amounts of carburizer is between 1.61-2.40ppm, and the average hydrogen content in the molten steel is 2.09ppm. Figure 2 It can be seen that the hydrogen content in the molten steel with different addition amounts of raw dolomite is between 1.6-2.5ppm, and the average hydrogen content in the molten steel is 2.05ppm. Figure 3 It can be seen that the hydrogen content in the molten steel with different addition amounts of sintered ore is between 1.4-2.4ppm, and the average hydrogen content in the molten steel is 1.89ppm. Figure 4 It can be seen that the hydrogen content in the molten steel with different addition amounts of light-burned magnesium balls is between 1.5-2.4ppm, and the average value of the hydrogen content in the molten steel is 1.86ppm. It can be seen that the effects of carburizer, raw dolomite, sintered ore and light-burned magnesium balls on the hydrogen content in the molten steel are not obvious. Figure 5 It can be seen that the hydrogen content in the molten steel fluctuates greatly under different addition amounts of top slag lime. When the addition amount of top slag lime in a single furnace is 400kg, the hydrogen content in the molten steel is 4.2-7.8ppm, and the average value of the hydrogen content in the molten steel is 5.53ppm; when the addition amount of top slag lime in a single furnace is 600kg, the hydrogen content in the molten steel is 5.2-8.3ppm, and the average value of the hydrogen content in the molten steel is 6.76ppm; when the addition amount of top slag lime in a single furnace is 800kg, the hydrogen content in the molten steel is 4.3-9.4ppm, and the average value of the hydrogen content in the molten steel is 6.92ppm. The average values ​​of the hydrogen content in the molten steel under different addition amounts of top slag lime are fitted, and the data fitting image is shown as follows. Figure 6 As shown by Figure 6It can be seen that the R square value is 0.9938 and the residual square is 0.066, indicating that the average amount of top slag lime added has a strong correlation with the hydrogen content in the molten steel. The only possible effect of top slag lime on the hydrogen content of molten steel is that CaO absorbs moisture and converts into Ca(OH)2.

[0041] The hydrogen content in the molten steel of each heat of repeat 1 to repeat 3 in experimental group 6 is shown in Table 3.

[0042] Table 3 Parameter values ​​of each heat in experimental group 6

[0043] It can be seen from Table 3 that, under the same addition time of top slag lime, the hydrogen content in the molten steel obtained by smelting with top slag lime with a discharge time of less than 4 hours is significantly lower than that obtained by smelting with top slag lime with a discharge time of more than 8 hours, indicating that the discharge time of top slag lime has a greater influence on the hydrogen content in the molten steel. When the discharge time of top slag lime is less than 4 hours, the hydrogen content in the molten steel of furnace 6-1>the hydrogen content in the molten steel of furnace 6-2>the hydrogen content in the molten steel of furnace 6-3, indicating that under the premise that the discharge time of top slag lime is less than 4 hours, the addition time of top slag lime has a greater influence on the hydrogen content in the molten steel, and adding top slag lime to the molten steel during the steel tapping process 3 minutes after the addition of deoxidizing alloy and after the completion of steel tapping can control the hydrogen content in the molten steel below 4.3ppm.

[0044] Example 2 Experiment on the correlation between atmospheric humidity, lime particle size and the conversion ratio of CaO in lime to Ca(OH)2 after moisture absorption After the top slag lime absorbs water, it is very easy to lose its reaction activity due to powderization. Therefore, this embodiment analyzes the correlation between atmospheric humidity, lime particle size and the conversion ratio of CaO in the lime to Ca(OH)2 after absorbing moisture through the moisture absorption rate of the top slag lime.

[0045] The small-particle top slag lime just fired in the lime kiln was divided into six groups according to the particle size, and marked as experimental group 1', experimental group 2', experimental group 3', experimental group 4', experimental group 5', and experimental group 6'. Among them, the average particle size of the top slag lime of experimental group 1'-experimental group 4' is 40mm, the average particle size of the top slag lime of experimental group 5' is 30mm, and the average particle size of the top slag lime of experimental group 6' is 20mm. The top slag lime of experimental group 1'-experimental group 3' was exposed to an environment with a humidity of 70%, 60%, and 50% for 24 hours for moisture absorption observation; the top slag lime of experimental group 4'-experimental group 6' was exposed to an environment with an atmospheric relative humidity of 60% for 24 hours for moisture absorption observation. During the moisture absorption observation process, the top slag lime of experimental group 1'-experimental group 6' was weighed every hour with an electronic scale and the data was recorded. The above test was repeated 3 times (3 days) using the same method, and the average value of weight change was taken as the data. The statistical graph of the average weight of the top slag lime of experimental group 1'-experimental group 3' changing with the blast time is shown in the figure below: Figure 7 As shown in the figure, the statistical graph of the average weight of the top slag lime of the experimental group 4' to the experimental group 6' changing with the burst time is as follows Figure 8 As shown, the moisture absorption rate of the top slag lime of experimental group 1'-experimental group 6' is as follows Fig. 9 shown.

[0046] Depend on Figure 7 and Figure 8 It can be seen that with the increase of relative humidity, the top slag lime absorbs moisture earlier, the moisture absorption capacity is stronger, and the moisture absorption rate is higher, which is consistent with the characteristics of the top slag lime itself; the larger the average particle size of the top slag lime, the earlier the moisture absorption is, the longer the moisture absorption lasts, the stronger the moisture absorption capacity is, and the higher the moisture absorption rate is. Fig. 9 It can be seen that in the first 8 hours of air exposure, the moisture absorption capacity of the top slag lime of experimental groups 1'-6' was comparable, and the moisture absorption rate was relatively stable; after 8 hours of air exposure, the higher the relative humidity of the atmosphere and the larger the particle size of the top slag lime, the greater the moisture absorption rate of the top slag lime. For example, the moisture absorption rate of the top slag lime of experimental group 4' gradually increased after 8 hours of air exposure, and the moisture absorption rate of the top slag lime of experimental group 4' reached the maximum value after 16 hours of air exposure; at the same time, under the condition of comparable relative humidity of the atmosphere, the moisture absorption rates of the top slag lime of experimental groups 2', 5', and 6' were comparable. This shows that the correlation of the moisture absorption rate of the top slag lime is ranked from strong to weak, first the relative humidity of the atmosphere, and second the average particle size of the top slag lime. Therefore, from the perspective of the geographical environment, steel enterprises in coastal and riverside cities with high humidity need to pay more attention to the moisture absorption degree of the top slag lime.

[0047] Example 3 The relative humidity R of the atmosphere is 71%. The charge of the converter is 180t of molten iron, 35t of scrap steel, 30t of iron blocks, 100kg of recarburizer, 2000kg of raw dolomite, 0kg of sintered ore, 1000kg of light-burned magnesium balls, and 700kg of top slag lime, of which the average particle size d of the top slag lime is 27mm. The top slag lime is added after the converter is tapped. The relative humidity R of the atmosphere and the average particle size d of the top slag lime are substituted into the following formula to calculate the range of the top slag lime discharge time T: ; T≤3.794h.

[0048] The time T of the top slag lime from leaving the warehouse to entering the converter is controlled within 3.79h. At this time, the water absorption ratio of the top slag lime is ≤0.6%. During the converter steel tapping process, argon gas is blown to the bottom of the ladle until the ladle is lifted. During the converter steel tapping process, the flow rate of argon gas blown to the bottom of the ladle is 80Nm 3 / h; 3-5min before the completion of steel tapping, the flow rate of argon gas at the bottom of the ladle is 70Nm 3 / h; from the end of steel tapping to the lifting of the ladle, the flow rate of argon gas blown to the bottom of the ladle is 40Nm 3 / h control. After the molten steel reaches the LF treatment position, the on-site Heraeus hydrogen determination system is used to detect the hydrogen content of the molten steel. The determined hydrogen value is 2.8ppm. During the LF refining process, slag making material is first added, and then argon gas is blown from the bottom of the ladle for stirring for 3-5 minutes. After the slag making material is fully melted, the temperature is raised and the power is turned on.

[0049] Example 4 The relative humidity R of the atmosphere is 77%. The charge of the converter is 192t of molten iron, 40t of scrap steel, 15t of iron block, 150kg of carburizer, 2300kg of raw dolomite, 700kg of sintered ore, 1800kg of light-burned magnesium balls, and 800kg of lime. The average particle size d of the top slag lime is 25mm. The top slag lime is added after the converter is tapped. The relative humidity R of the atmosphere and the average particle size d of the top slag lime are substituted into the following formula to calculate the range of the top slag lime discharge time T: ; T≤3.155h.

[0050] The time T of the top slag lime from leaving the warehouse to entering the converter is controlled within 3.155h. At this time, the water absorption ratio of the top slag lime is ≤0.6%. During the converter steel tapping process, argon gas is blown to the bottom of the ladle until the ladle is lifted. During the converter steel tapping process, the flow rate of argon gas blown to the bottom of the ladle is 80Nm 3 / h; within 3 minutes before the completion of steel tapping, the flow rate of argon gas at the bottom of the ladle is 80Nm 3 / h; from the end of steel tapping to the lifting of the ladle, the flow rate of argon gas blown to the bottom of the ladle is 40Nm 3 / h control. After the molten steel reaches the LF treatment position, the on-site Heraeus hydrogen determination system is used to detect the hydrogen content of the molten steel. The hydrogen determination value is 2.3ppm. During the LF refining process, slag making material is first added, and then argon gas is blown from the bottom of the ladle for stirring for 3-5 minutes. After the slag making material is fully melted, the temperature is raised and the power is turned on.

[0051] Although the present invention has been described in detail with reference to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art may easily think of changes or substitutions within the technical scope disclosed by the present invention, and these shall be within the scope of protection of the present invention.

Claims

1. A method for effectively controlling abnormally high hydrogen content in molten steel, characterized in that: After the converter smelting is completed, the amount of top slag lime added is 400-1000kg; the particle size of the top slag lime is 20-30mm; the time T for the top slag lime to be discharged from the warehouse is controlled within the following range: ; Among them, the unit of T is h; R is the relative humidity of the atmosphere; d is the average particle size of the top slag lime, in mm; after control, the hydrogen content in the molten steel reaching the LF refining furnace is ≤4.3ppm.

2. A method for effectively controlling abnormally high hydrogen content in molten steel as claimed in claim 1, characterized in that: Top slag lime is added during the steel-making process 3 minutes after the deoxidizing alloy is added or after the converter steel-making is completed.

3. A method for effectively controlling abnormally high hydrogen content in molten steel as claimed in claim 1, characterized in that: The out-of-warehouse time T is the time that the top slag lime is exposed to the atmosphere from the time it is out of the warehouse, and the relative humidity of the atmosphere is 50%-80%.

4. A method for effectively controlling abnormally high hydrogen content in molten steel as claimed in claim 1, characterized in that: During the steel tapping process of the converter, argon is blown into the bottom of the ladle until the ladle begins to be lifted.

5. A method for effectively controlling abnormally high hydrogen content in molten steel as claimed in claim 4, characterized in that: The flow rate of bottom blowing argon is 40-80Nm 3 / h.

6. A method for effectively controlling abnormally high hydrogen content in molten steel as claimed in claim 5, characterized in that: During the steel tapping process, the flow rate of argon gas blown from the bottom of the ladle is 60-80Nm 3 / h; 3-5min before the completion of steel tapping, the flow rate of argon gas at the bottom of the ladle is 60-80Nm 3 / h; from the end of steel tapping to the start of lifting the ladle, the flow rate of argon gas blowing from the bottom of the ladle is 40-60Nm 3 / h.

7. A method for effectively controlling abnormally high hydrogen content in molten steel as claimed in claim 4, characterized in that: The ladle is lifted and transported to the LF refining furnace for refining.

8. A method for effectively controlling abnormally high hydrogen content in molten steel as claimed in claim 7, characterized in that: After control, the hydrogen content in the molten steel reaching the LF refining furnace is 2.3-2.8ppm.

9. A method for effectively controlling abnormally high hydrogen content in molten steel as claimed in claim 7, characterized in that: After the molten steel arrives at the LF refining furnace, slag-making material is added first, and then argon blowing from the bottom of the ladle is started to stir for 3-5 minutes. After the slag-making material is fully melted, the temperature is raised and the power is turned on.

Citation Information

Patent Citations

  • A method for producing ultra-low hydrogen content steel under non-vacuum conditions

    CN117305536B